The Current Situation of Angora Goat As a Geographical Symbol - (:unkn) unknown (MILLI FOLKLOR DERGISI, 2013)
Anatolian, especially Ankara and its close territory, where comes to the mind as the place of Angora goat's (Capra hircus ancryrensis) cultivating in the world, has unfortunately lost its superiority recently. It has not only wiped through Ankara and its territory, in all Turkiye this cultural value has been dramatically extincted from agricultural life. Although our country contains optimum oppurtunity for the cultivating of Angora goat in terms of geographical conditions, it has placed behind the countries, to which the discussed animal was taken afterwards. In addition to that, although it is cultivated in foreigner regions having the same geographical conditions as in Central Anatolia Region, it's know that when the amount of the mohair is compared with the amount in our country, it is much more lower. However, while Angora goat's number was over 1 million at the beginning of 1990's, this number has fallen in 90% rates in the last 20 years. As a natural consequence of this decline occurring within our Angora goat wealth, and also has experienced a decline in the mohair production and the products which obtained from mohair. At the same time this decline that in activity in question has shown effect in the cultural life, too. The various textiles which obtained from mohair and traditional products had almost begun to be forgotten. In this study, the situation that our wealth of Ankara goat, which is nearly extincted and is the symbol of primary Ankara and then all of the Turkiye, is dealt with.
Keywords: Angora goat; Mohair; Geographical symbol; Agricultural geography; Cultural economy; Turkiye